DESCARTES ON THE PHENOMENON OF MAN AND THE BOUNDARIES OF DOUBT - A. M. Malivskyi (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose of the article is to reconstruct the ideological and philosophical context in which Descartes actualizes the phenomenon of man and the task of refuting scepticism. A precondition for its implementation is attention to the explication of the peculiarities of reception by researchers of scepticism and the doctrine of doubt; delineation of the semantic implications of the anthropological intention of philosophizing and the boundaries of doubt. Theoretical basis. I base my view of Descartes’ legacy on the conceptual positions of phenomenology, existentialism and hermeneutics. Originality. Based on the tendency of anthropologization of Descartes’ basic project, I refute the widespread tendency to qualify Descartes’ position as a sceptic, which is based on superficial stereotypes about the impersonality of his philosophy. The modern reception of the thinker’s texts indicates the priority for him of the task of explicating the conditions of man’s realization of his own vocation in the Universe, which is supplemented by the idea of the limits of science and the doubt correlative to it. Accordingly, Descartes’ refutation of scepticism appears in the form of concern for the creation of favourable conditions for human self-development, which implies a restrained attitude to the spheres of morality and religion. Conclusions. The author based on his own interpretation of the philosophical searching of the thinker attempted to rehabilitate Descartes’ position on scepticism. An appeal to the texts of the French philosopher shows that doubt is for him a means of creating conditions for the representation of the human in man. A deeper meaningful clarification of the method chosen by Descartes to refute scepticism involves appeal to the will and practical mastery of a new system of semantic coordinates of life.